2016
DOI: 10.1080/15384101.2015.1121328
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase-mediated phosphorylation of breast cancer metastasis suppressor 1 (BRMS1) affects cell migration

Abstract: Expression of Breast Cancer Metastasis Suppressor 1 (BRMS1) reduces the incidence of metastasis in many human cancers, without affecting tumorigenesis. BRMS1 carries out this function through several mechanisms, including regulation of gene expression by binding to the mSin3/histone deacetylase (HDAC) transcriptional repressor complex. In the present study, we show that BRMS1 is a novel substrate of Cyclin-Dependent Kinase 2 (CDK2) that is phosphorylated on serine 237 (S237). Although CDKs are known to regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 97 publications
(138 reference statements)
1
13
0
Order By: Relevance
“…6 There are still open questions about how S237 phosphorylation alters the function of BRMS1, as mutation of this site does not affect BRMS1 localization, binding to the HDAC complex or RBP1 protein, or the transcriptional regulation of osteopontin by BRMS1. 3 As observed by the authors, the S237 site is immediately proximate to the site of an NLS2 putative nuclear localization signal which is known to be important to the ability of BRMS1 to suppress metastasis, and this bears further investigation. More recently, it has been found that BRMS1 acts as a ubiquitin ligase toward the p300 histone acetyltransferase where alteration of this ubiquitin ligase activity increases metastasis, 7 and this is another possible function of BRMS1 that may be modulated by S237 phosphorylation.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…6 There are still open questions about how S237 phosphorylation alters the function of BRMS1, as mutation of this site does not affect BRMS1 localization, binding to the HDAC complex or RBP1 protein, or the transcriptional regulation of osteopontin by BRMS1. 3 As observed by the authors, the S237 site is immediately proximate to the site of an NLS2 putative nuclear localization signal which is known to be important to the ability of BRMS1 to suppress metastasis, and this bears further investigation. More recently, it has been found that BRMS1 acts as a ubiquitin ligase toward the p300 histone acetyltransferase where alteration of this ubiquitin ligase activity increases metastasis, 7 and this is another possible function of BRMS1 that may be modulated by S237 phosphorylation.…”
mentioning
confidence: 72%
“…Consistent with our current knowledge of BRMS1 as a metastasis suppressor that does not influence primary tumor growth, Roesley et al also show that overexpression of BRMS1 S237D (which mimics the constitutively phosphorylated protein) did not suppress the proliferation or colony forming potential of cancer cells. 3 This is an important finding as it suggests that high CDK2 activity may suppress invasion and metastasis via BRMS1, though paradoxically high CDK2 activity is normally assumed to be tumorigenic. However, since the initiation of a primary tumor and metastasis are distinct processes, it is not surprising that multifunctional master regulators such as cyclins and CDKs can play different roles in these disease stages, resulting in temporal changes to their expression as disease progresses.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Rb protein acts as a tumor suppressor controlling G1/S transition of cell cycle. 27 When Rb is phosphorylated, it loses its negative control on G1/S transition. 28 Hence, activating E2F family of transcription factors that allows DNA replication to start.…”
Section: Cdk Role In Cell Cyclementioning
confidence: 99%
“…Breast cancer metastasis suppressor 1 (BRMS1) was first discovered for its significant inhibition of metastasis in breast cancer cells (1). Depending on the cell types used, BRMS1 has been noted to inhibit multiple steps in the invasion-metastasis cascade, including cell communication (2,3), cell migration (4,5), cell apoptosis (6,7), epithelial-mesenchymal transition (EMT) (8), among others. Several important BRMS1-interacting proteins have been identified, providing possible clues to the molecular mechanisms of action of BRMS1.…”
Section: Introductionmentioning
confidence: 99%